Noninvasive Optical Measurements of Dynamic Cerebral Autoregulation by Inducing Oscillatory Cerebral Hemodynamics. - Pham, Thao.; Fernandez, Cristianne.; Blaney, Giles.; Tgavalekos, Kristen.; Sassaroli, Angelo.; Cai, Xuemei.; Bibu, Steve.; Kornbluth, Joshua.; Fantini, Sergio. (Tufts University. Tisch Library., 2023)
Cerebral autoregulation limits the variability of cerebral blood flow (CBF) in the presence of systemic arterial blood pressure (ABP) changes. Monitoring cerebral autoregulation is important in the Neurocritical Care Unit (NCCU) to assess cerebral health. Here, our goal is to identify optimal frequency-domain near-infrared spectroscopy (FD-NIRS) parameters and apply a hemodynamic model of coherent hemodynamics spectroscopy (CHS) to assess cerebral autoregulation in healthy adult subjects and NCCU patients.; Keywords: cerebral autoregulation, cerebral blood flow, near-infrared spectroscopy, frequency-domain, coherent hemodynamics, neurocritical care, brain, oscillations.; Funding for open access publishing provided by the Tisch Library Open Access Publishing Fund